Harmonisasi Pengujian Peraturan oleh Mahkamah Konstitusi dan Mahkamah Agung sebagai Upaya Peningkatan Kepastian Hukum dan Perlindungan Konstitusional - Adhe Permana; Rendhi Renaldhi; Siti Nur Ambarini; Iyus YL Tobing; Ihsan Sanjaya; Sena Narenda; Firman Adi Candra (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
The division of authority for judicial review of regulations between the Constitutional Court (MK) and the Supreme Court (MA) often leads to overlapping jurisdiction, differing standards of review, and inconsistent rulings. This situation weakens legal certainty and constitutional protection, which should form the foundation of a rule of law state. This research analyzes the source of this disharmony using a normative legal method with statutory and conceptual approaches. The study's findings indicate the absence of an integrative mechanism between the two institutions to ensure the alignment of review parameters. Therefore, a harmonization model is required to clearly define the boundaries of authority, synchronize the standards of review, and strengthen the coordination of rulings. This harmonization is projected to enhance the effectiveness of constitutional control and guarantee the protection of citizens' rights more consistently.